Philippine Government and Constitution - Garcia, Carlito D. (Manadaluyong City, Philippines; Books ATBP. Publishing Corp., 2015)
Government Constitution falls in the domain of political science as a discipline. It deals with the study of city and states. It's essential nature, form manifestation, organization and development.
Includes bibliographical references.
Keywords: Political Science